2018
DOI: 10.18632/oncotarget.24804
|View full text |Cite
|
Sign up to set email alerts
|

Increased gut permeability in cancer cachexia: mechanisms and clinical relevance

Abstract: Intestinal disorders often occur in cancer patients, in association with body weight loss, and this alteration is commonly attributed to the chemotherapy. Here, using a mouse model of cancer cachexia induced by ectopic transplantation of C26 cancer cells, we discovered a profound alteration in the gut functions (gut permeability, epithelial turnover, gut immunity, microbial dysbiosis) independently of any chemotherapy. These alterations occurred independently of anorexia and were driven by interleukin 6. Gut d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(127 citation statements)
references
References 63 publications
11
116
0
Order By: Relevance
“…Arguing against this and supporting a systemic effect also in gastrointestinal cancer, increased gut leakage is also apparent in an additional mouse model where colon cancer cells are injected subcutaneously, excluding a direct mechanical effect of the primary tumor. In the latter study, gut integrity is restored by treatment with an anti‐IL‐6 antibody, demonstrating the involvement of the inflammatory system in intestinal dysfunction in cachexia . Inflammation therefore seems to be both cause and consequence of gut dysfunction, at least in rodent models.…”
Section: Absorption/malabsorption Of Energy Substratesmentioning
confidence: 80%
“…Arguing against this and supporting a systemic effect also in gastrointestinal cancer, increased gut leakage is also apparent in an additional mouse model where colon cancer cells are injected subcutaneously, excluding a direct mechanical effect of the primary tumor. In the latter study, gut integrity is restored by treatment with an anti‐IL‐6 antibody, demonstrating the involvement of the inflammatory system in intestinal dysfunction in cachexia . Inflammation therefore seems to be both cause and consequence of gut dysfunction, at least in rodent models.…”
Section: Absorption/malabsorption Of Energy Substratesmentioning
confidence: 80%
“…include cardiovascular and lung disorders, diabetes, and cancer. 65 Many of the specific medical conditions that are included within these groups of disorders are linked to an elevation in gut dysbiosis/ permeability, 66,67 mitochondrial dysfunction, 68 and circadian dysregulation, 69,70 with melatonin showing utility in their management. 71,72 Ageing, the main risk factor for death from influenza and covid-19, is highly associated with these pathophysiological changes, [73][74][75][76] with melatonin, partly via sirtuin induction as well as circadian and mitochondria regulation, attenuating ageing-associated processes.…”
Section: Preexisting Medical Conditionsmentioning
confidence: 99%
“…Bindels et al further evaluated the interactions between cancer cachexia, gut barrier dysfunction and the microbiome through both human and animal studies [38]. Their mouse model for cancer cachexia was generated by the ectopic transplantation of C26 colon carcinoma cells.…”
Section: Gut Barrier Dysfunctionmentioning
confidence: 99%
“…Additional multivariate analysis revealed that increased LBP was significantly predictive of poor outcome in cancer patients. It was proposed that in the future LBP might be utilized as a biomarker in cancer cachexia [38]. Given this data, it is conceivable that the immune dysfunction may be both a cause and an effect of intestinal dysfunction and subsequent bacterial translocation.…”
Section: Gut Barrier Dysfunctionmentioning
confidence: 99%